Histological Variation in Blubber Morphology of the Endangered East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) with Ontogeny and Reproductive States - Ji, Junhua (Zool Stud, 2019)
The highly lipid-rich blubber in the hypodermis is a specialized structure that functions in thermoregulation, energy storage, buoyancy control, locomotion, and streamlining the body shape in marine mammals. The key objective of this study was to investigate blubber development in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) across the ontogenetic (fetuses, calves, and adults) and reproductive states (adults, pregnant, and lactating). Blubber samples were collected from East Asian Finless Porpoises (EAFP) that were accidentally caught in the fishing nets in the Bohai/Yellow Sea from late April to mid May of 2015. The mean blubber depth was significantly thinner in fetuses across the ontogenetic groups and significantly thicker in pregnant and lactating vs. adult females across the reproductive states. Across the four regions in each group, we did not find significant variations in blubber depth. However, the correlations between body length and weight vs. blubber depth was significant. Histological observation identified three layers of stratified blubber with a significantly smaller adipocyte cell size in fetuses and a significantly higher area ratio of structural fiber in the middle and inner layers across the ontogenetic groups. Across the reproductive states, we did not observe a statistically significant difference in the adipocyte cell size or area ratio of the structural fiber. Our results suggest that prenatal blubber growth is characterized by an increase in the adipocyte cell count, while postnatal growth is the result of an increase in cell size. They also indicate that ontogeny can affect blubber depths and cellular measurements in the EAFP.